An investigation on the impact of landownership dynamics in rural development: A case of Nooitgedacht area in Muldersdrift, Mogale City Local Municipality - Masonganye, Thoriso Obakeng (University of the Witwatersrand, Johannesburg, 2024)
South Africa's history of land ownership is deeply intertwined with the legacy of colonialism and segregation. In the contemporary context, land ownership has emerged as a pivotal catalyst for rural development, aimed at addressing historical injustices and fostering sustainable socio-economic growth. Despite numerous reforms and initiatives introduced since the dawn of democracy, challenges persist, particularly in rural regions like Nooitgedacht in the West of Gauteng. In Nooitgedacht, landlessness, underdevelopment, poverty, and minimal economic activity continue to plague the community. This study delves into the intricate relationship between land ownership dynamics and rural development, with a specific focus on Nooitgedacht within the Mogale City Local Municipality. To comprehensively assess this issue, a multi-faceted research approach was employed, incorporating primary and secondary data collection methods. The research methods encompassed a thorough desktop survey, the distribution of questionnaires to community members, and in-depth interviews with municipal officials and community stakeholders. The desktop survey harnessed municipal valuation data to discern the existing patterns of land ownership in Nooitgedacht, revealing a marked imbalance, with most of the land controlled by private individuals and businesses, while national, provincial, and local governments held relatively merger land ownership within the study area. This skewed ownership pattern underscores the profound challenge of land access in Nooitgedacht. Consequently, the area grapples with persistent land inequalities encompassing issues of access, ownership, distribution, and administration, which further manifest through ongoing threats of land invasions, evictions, limited development, and a dearth of economic activities. Despite the presence of municipal policies aimed at addressing these disparities, implementation remains sporadic, fragmented, and inadequately coordinated within the municipality, resulting in a sluggish delivery of rural development. In conclusion, the study underscores the pivotal role of land ownership in shaping the trajectory of rural development in Nooitgedacht. It is evident that without equitable and well-coordinated land ownership policies and practices, the goal of achieving sustainable rural development in this region remains an elusive aspiration.
A dissertation submitted to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master in Development Planning in 2024.
Keywords: Land; Land ownerships; Rural Development; Mogale City Local Municipality; Nooitgedacht; West of Gauteng; South Africa; UCTD; SDG-17: Partnerships for the goals; SDG-8: Decent work and economic growth